2001
DOI: 10.1002/jbm.1065
|View full text |Cite
|
Sign up to set email alerts
|

Surface and biological evaluation of hydroxyapatite‐based coatings on titanium deposited by different techniques

Abstract: Hydroxyapatite coatings have been deposited on titanium cp by plasma spray, sol-gel, and sputtering techniques for dental implant applications. The latter two techniques are of current interest, as they allow coatings of micrometer dimensions to be deposited. Coating morphology, composition, and structure have been investigated by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). All coatings were homogeneous and exhibited a rough morphology suitable for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 21 publications
3
82
0
Order By: Relevance
“…Similar to the results of our study, several short-term in vitro assays demonstrated that the coated HAp with the micro-roughened surface suppresses the cell adhesion and proliferation, while stimulating the differentiated cell function [59][60][61]. On the other hand, it has been reported that the higher surface area from the micro-roughness is one of the most effective factors for accelerating osseointegration of implant material during long-term implantation in the body.…”
Section: Alp Activity Of Mg-63 Cells Cultured On Cap-coated Hnssupporting
confidence: 90%
“…Similar to the results of our study, several short-term in vitro assays demonstrated that the coated HAp with the micro-roughened surface suppresses the cell adhesion and proliferation, while stimulating the differentiated cell function [59][60][61]. On the other hand, it has been reported that the higher surface area from the micro-roughness is one of the most effective factors for accelerating osseointegration of implant material during long-term implantation in the body.…”
Section: Alp Activity Of Mg-63 Cells Cultured On Cap-coated Hnssupporting
confidence: 90%
“…However, Kumar et al have shown that brushite is soluble in aqueous solutions and (the more stable) HA is subsequently precipitated onto the surface [34]. Air-exposed bulk HA samples show an XPS determined Ca/P ratio close to or slightly lower than the stoichiometric value of 1.67 [32,33,35], whereas a significant reduction in the Ca/P ratio (values close to 1.0) has been found in this and other XPS studies of HA formation in aqueous and physiological solutions [36][37][38]. Amrah-Bouali et al [38] have studied the Ca/P ratio determined by XPS for HA exposed to a range of aqueous and physiological solutions and found that in all cases that the Ca/P ratio after exposure approaches 1.0.…”
Section: Xps Resultsmentioning
confidence: 99%
“…Various Ti implant modifications including plasma-spraying, ion-beam assisted deposition and coating with calcium phosphate or bioactive glass have been developed to assist in improving this osseointegration process [10]. In this work, sol-gel processing was used to manufacture four different HA/TiO2 surface coatings on Ti, which had previously shown promise over untreated The sol-gel coatings used herein showed uniform coating thickness and similar ranges of roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Sol-gel methods additionally have a practical advantage of being applicable at mass-production level and of being a simple, relatively low temperature means of surface modification for complex implant shapes [10].…”
Section: Introductionmentioning
confidence: 99%